BRS Sampa: malting barley cultivar for irrigated production - Euclydes Minella; Luiz Eichelberger; Leila M. Costamilan; Sandra M. M. Scagliusi (Crop Breeding and Applied Biotechnology, 2015)
Barley BRS Sampa is a late heading, dwarf two-rowed malting barley cultivar released for irrigated production in Brazil. It combines high yield and kernel plumpness, disease and lodging resistance with malting quality. It is adapted to all major irrigated production regions of Brazil.